Cho hàm số $f(x)=(m-1)x^4-2mx^2+1$ với $m$ là tham số thực. Nếu $\min\limits_{[0;3]}f(x)=f(2)$ thì $\max\limits_{[0;3]}f(x)$ bằng
$-\dfrac{13}{3}$ | |
$4$ | |
$-\dfrac{14}{3}$ | |
$1$ |
Chọn phương án B.
$\blacksquare$ Với $m=1$: $f(x)=-2x^2+1$.
Ta có $f'(x)=-4x$. Cho $f'(x)=0\Leftrightarrow x=0\in[0;3]$.
Lại có $f(0)=1$, $f(3)=-17$, $f(2)=-7$. Suy ra $\min\limits_{[0;3]}f(x)=f(3)$.
Vậy $m=1$ không thỏa đề bài.
$\blacksquare$ Với $m\neq1$, ta có $f'(x)=4(m-1)x^3-4mx$.
Cho $f'(x)=0\Leftrightarrow\left[\begin{array}{l}x=0\\ x=\pm\sqrt{\dfrac{m}{m-1}}\end{array}\right.$
Vì $\min\limits_{[0;3]}f(x)=f(2)$ nên $x=2$ là một nghiệm của phương trình $f'(x)=0$, tức là $$\begin{aligned}
\pm\sqrt{\dfrac{m}{m-1}}=2&\Leftrightarrow\dfrac{m}{m-1}=4\\
&\Leftrightarrow m=4(m-1)\\
&\Leftrightarrow m=\dfrac{4}{3}.
\end{aligned}$$
Khi đó $f(x)=\dfrac{1}{3}x^4-\dfrac{8}{3}x^2+1$.
Ta có $f(0)=1$, $f(3)=4$. Suy ra $\max\limits_{[0;3]}f(x)=4$.